Ethics-based learning materials in primary schools in Indonesia - Muzaki, Ferril Irham (University of Las Palmas de Gran Gran Canaria, 2022)
This review paper will discuss on ethics-based learning materials for primary schools' students in Indonesia. Ethical based learningoriented learning is an idea to develop skills in building the ability to lead students to have skills in developing behavior. In line with this, Ethical development-based learning is an activity that is to develop the identity and personality of students in the elementary school. Similarly, the ability to develop skills and skills in discourse and ideas, appropriate skills despite attention to the ability to adjust proficiency in discourse or use ideas that fit with the skills in discourse. The ability to lead and understand that the appropriate skills despite attention to the data that exist among learners. In this case the ability to develop the ability to adjust Keywords: Ethical development, Life-Based Learning, Educational Discourse Morals or what is commonly referred to as character is an ideal idea in conducting data to develop writing skills and skills. In this case, the ability to build knowledge and ideas is reflected in skills that adapt to the environment with a national perspective. Nasution (2017:3) states in this case the skill to promote ethical development is the skill to build dignified development ideas, in this case the ability to develop knowledge and ideas is an effort to build performance on the scientific performance of a student who is in elementary school (Bryan & Burstow, 2018). In line with this, the ability to develop ideas is reflected in developing skills in developing adequate scientific ideas in the elementary school environment (Anggraini et al., 2016). This is reflected in the ability to develop ideas to adapt to an adequate environment with the ability to be friendly with the Ethical development environment. In developing skills to develop adequate scientific ideas, it is necessary to understand the concept of adequate ethical development in social life in society. The ability to develop ideas is a skill that reflects the ability to develop social skills. The concept of Ethical development is a way and ideas to adjust understanding in building skills that adapt and ideas with the existing environment (Falabella, 2020). The capability to adapt are inseparable in ethical development-oriented learning. Ethical development is part of learning in elementary schools even though it pays attention to abilities and skills in independent ideas that already exist.in line with Arifkha, et al (2017:2). When the development of adequate abilities, skills to develop adequate knowledge for learners to be in the idea that corresponds to the knowledge of Ethical development. Knowledge to develop ideas is a skill in understanding knowledge to change in the sense of developing adequate knowledge. In this case, the ability to develop adequate ideas is an adequate idea in the midst of globalization (Katranci et al., 2015).